The determinants of tax revenue: A study of Southeast Asia - Nguyen Minh Ha; Pham Tan Minh; Quan Minh Quoc Binh (Cogent Economics & Finance, 2022)
This study identifies the determinants of tax revenue in Southeast Asia based on a balanced dataset of eight countries. By employing static (pooled Ordinary Least Squares (OLS), fixed effects (FE) model, random effects (RE) model and Driscoll-Kraay standard error) as well as dynamic panel data (system-generalized method of moments) regression techniques, we show that the openness of the economy, foreign direct investment (FDI), the ratio of foreign debt to the gross domestic product (GDP), the share of value added in industry to GDP have positive impacts on tax revenue, and official development assistance has a negative impact. We suggest that Southeast Asian countries design better policies in international trade as well as attract FDI, speed up the process of economic restructuring, and enhance the capacity to mobilize, manage, and use foreign debt and assistance in order to collect more taxes.
Keywords: H2; O1; O2; 330; Driscoll-Kraay; determinants of tax revenue; Southeast Asia; system-GMM